2016
DOI: 10.1002/ppsc.201600216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Novel Ternary Hematite Nanocomposites Structure with Fullerene and 2D-Electrochemical Reduced Graphene Oxide for Superior Photoelectrochemical Performance

Abstract: In this study, a novel ternary hematite nanocomposites photoanode structure with superior photoelectrochemical (PEC) performance consisting of fullerene (C60) and 2D‐electrochemical reduced graphene oxide (eRGO) used as the effective surface passivators is developed. The introduction of both the electron scavenging C60 and highly conducting eRGO has mitigated the high interfacial recombination rate of hematite and led to the superior enhancement in PEC performance. UV–vis analysis reveals that the incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…These ultrathin g-C 3 N 4 nanolayers can not only restrain the interfacial charge recombination of BiVO 4 , but also promote the transformation and storage of photogenerated holes for water oxidation. Very recently, a novel ternary hematite photoanode with fullerene and 2D-electrochemical rGO was designed by Phuan et al, [234] as shown in Figure 17d, the introduction of C60 and rGO contributes to a 16.8-fold enhancement in photocurrent density and a 0.8-fold reduction in charge transfer resistance in comparison with the pure hematite photoanode. Under simulated solar irradiation, the photocurrent density of N-CDs@α-Fe 2 O 3 /Ti photoanode shows a 3.4-fold increment with a 280 mV negative shift of the onset potential and better durability compared with that of pristine α-Fe 2 O 3 /Ti.…”
Section: Metal-free Cocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…These ultrathin g-C 3 N 4 nanolayers can not only restrain the interfacial charge recombination of BiVO 4 , but also promote the transformation and storage of photogenerated holes for water oxidation. Very recently, a novel ternary hematite photoanode with fullerene and 2D-electrochemical rGO was designed by Phuan et al, [234] as shown in Figure 17d, the introduction of C60 and rGO contributes to a 16.8-fold enhancement in photocurrent density and a 0.8-fold reduction in charge transfer resistance in comparison with the pure hematite photoanode. Under simulated solar irradiation, the photocurrent density of N-CDs@α-Fe 2 O 3 /Ti photoanode shows a 3.4-fold increment with a 280 mV negative shift of the onset potential and better durability compared with that of pristine α-Fe 2 O 3 /Ti.…”
Section: Metal-free Cocatalystsmentioning
confidence: 99%
“…Sci. [234] Copyright 2017, Wiley-VCH. a) J-V curves of the bare hematite and eRGO hematite-i nanocomposites.…”
Section: Non-noble Metal Atomsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to structural modifications, the influence of surface passivation and nanoparticle decoration on hematite photoanodes has been a subject of interest. Ternary hematite nanocomposite structures with fullerene and 2D-electrochemical reduced graphene oxide have been developed to achieve superior photoelectrochemical performance [57]. Moreover, the influence of the magnetic field and nanoparticle concentration on the thin film colloidal deposition process of magnetic nanoparticles has been studied to optimize the efficiency of hematite photoanodes [58].…”
Section: Photoanodes For Water Splittingmentioning
confidence: 99%